Predictive Factors For Severe And Critical Coronavirus Disease-19 In Young Adults - Elif Köse; Gökcen Gürkök Budak; Hüseyin Doğuş Okan; Aylin Çalıca Utku; Aziz Öğütlü; Ertuğrul Güçlü; Oğuz Karabay; Aslı Vatan (Sakarya Tıp Dergisi)
Purpose: Advanced age is associated with a poor prognosis in Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The present study investigated the predictive factors for disease severity in young adults.Method: Our study is a descriptive cross-sectional study. A total of 399 patients with SARS-CoV-2 aged under 60 who had been hospitalized at our hospital were retrospectively evaluated. Patients were stratified into mild, moderate, severe, and critical groups according to their respiratory rate, SpO2, and PaO2/FiO2 levels. The relationship between the signs and symptoms on hospital admission and the disease severity was evaluated.Results: The patients were classified as mild (n:112), moderate (n:192), severe and critical (n:95) according to disease severity. The mean age was 44. 43 of 399 patients were followed in the intensive care unit, and 17 patients died. According to the binary logistic regression analysis, advanced age, hypertension, dyspnea on admission, elevated CRP, decreased lymphocyte and eosinophil count, multiple bilateral ground glass appearances, and consolidation independently predicted the severity of the disease.Conclusion: The signs and symptoms should be evaluated in detail also in young patients with SARS-CoV-2. If risk factors are detected, they should be monitored more closely to predict a poor prognosis..